2021
DOI: 10.3390/biomedicines9070783
|View full text |Cite
|
Sign up to set email alerts
|

The Oscillatory Profile Induced by the Anxiogenic Drug FG-7142 in the Amygdala–Hippocampal Network Is Reversed by Infralimbic Deep Brain Stimulation: Relevance for Mood Disorders

Abstract: Anxiety and depression exhibit high comorbidity and share the alteration of the amygdala–hippocampal–prefrontal network, playing different roles in the ventral and dorsal hippocampi. Deep brain stimulation of the infralimbic cortex in rodents or the human equivalent—the subgenual cingulate cortex—constitutes a fast antidepressant treatment. The aim of this work was: (1) to describe the oscillatory profile in a rodent model of anxiety, and (2) to deepen the therapeutic basis of infralimbic deep brain stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 185 publications
2
21
0
5
Order By: Relevance
“…The model exhibits the predominance of certain frequency bands during the anxiogenic state and the activation of subnetworks with specific oscillatory patterns. The study reported that the deep brain stimulation of the infralimbic cortex reversed the oscillatory pattern, restoring the communication of the amygdala–hippocampal network [ 45 ].…”
mentioning
confidence: 99%
“…The model exhibits the predominance of certain frequency bands during the anxiogenic state and the activation of subnetworks with specific oscillatory patterns. The study reported that the deep brain stimulation of the infralimbic cortex reversed the oscillatory pattern, restoring the communication of the amygdala–hippocampal network [ 45 ].…”
mentioning
confidence: 99%
“…Preclinical translational animal studies play a major role in neuroscience research to understand the roles of neuropeptides, neurohormones, and endogenous biomolecules in the normal function of human life such as cognition, emotion, and social interaction, and in pathological alterations developing into neurological and psychiatric disorders [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97]. Various bioactive molecules are synthesized in the Try-KYN metabolic system.…”
Section: Discussionmentioning
confidence: 99%
“…Devido a problemas técnicos, os pesquisadores usaram dois amplificadores diferentes. Assim, os sinais foram amostrados a 250Hz por canal quando amplificados pelo amplificador Amps 300 e a 500Hz por canal quando amplificados pelo amplificador Amps 400 14 13 , do MEG 15 e do ECoG 10,16 .…”
Section: Introductionunclassified